Pengambilan Keputusan Dan Kebijakan Peningkatan Mutu Pendidikan Di SMP Negeri 15 Islam Terpadu Binjai - Muslim Muslim (LPPPI Publishing, 2022)
Quality education basically produces quality human resources as well. The quality of education is determined by various elements, namely school, community, and family involvement. In making a quality school, it is necessary to have a quality policy in schools. Quality policy in schools is an official and written policy of a school where school members are committed to realizing the policy. In making decisions and policies on the quality of education at SMP Negeri 15 Islam Terpadu Binjai, the principal together with the teachers develop and improve the quality of the school by conducting deliberation to formulate the vision, mission and goals of the school to be achieved. Then a better policy is made that serves as a guide for the direction of long-term school policies in terms of continuous quality improvement. Thus, in decision making and policies at SMP Negeri 15 Islam Terpadu Binjai, there is a process in improving the quality of education in order to achieve school education goals as expected.